Primary Retrobulbar Leiomyosarcoma in a Dog: A Case Report - Joong-Hyun Song; Do-Hyeon Yu; Dong-In Jung (Veterinary Sciences, 2020)
A 2-year-old female Mongrel dog weighing 3.12 kg presented with a 2-month history of progressive exophthalmos of the left eye and periorbital swelling. Fine-needle aspiration cytology of the affected tissue revealed atypical cells of suspected malignant mesenchymal tumor origin. Computed tomography and magnetic resonance imaging revealed an ill-demarcated soft tissue mass in the left retrobulbar space extending into the nasal cavity and into the frontal lobes of the brain with destruction of the adjacent cribriform plate and the basisphenoid bone. Histopathological features of the tumor were consistent with the diagnosis of undifferentiated sarcoma. The tumor cells were immunoreactive for vimentin, smooth muscle actin, and desmin and negative for S100. These findings were mostly consistent with leiomyosarcoma arising from the smooth muscle on the retrobulbar tissues. Primary retrobulbar leiomyosarcoma is an extremely rare tumor in dogs. To expand our knowledge of retrobulbar leiomyosarcoma in dogs, we have described its clinical, diagnostic imaging, histopathological, and immunohistochemical characteristics in a dog.